Penerapan House of Quality (HoQ) Untuk Peningkatan Kualitas Produk Pada UMKM Salad Buah di Kota Batam - Sumitro; Lawi, Ansarullah (Greeners: Journal of Green Engineering for Sustainability, 2024)
Fruit Salad SMEs in Batam City face significant challenges in improving product quality and services to meet customer needs. This study aims to identify and analyze the needs of customers of Fruit Salad SMEs in Batam City and formulate quality improvement strategies using the House of Quality (HoQ) tool. Data were obtained through surveys and analyzed using Pearson correlation to ensure validity and reliability. The results show that all items have a significant correlation with the total score, with correlation values ranging from 0.697 to 0.860 and p-values < 0.05, indicating strong data validity and reliability. Specifically, the item "Price appropriate to quality" showed the highest correlation at 0.860, while "Ease of ordering" had the lowest at 0.697. The analysis confirmed that the formulated strategies based on customer needs can be relied upon to enhance the competitiveness of Fruit Salad SMEs in Batam City. The application of the HoQ tool provided a clear prioritization of quality attributes, allowing SMEs to focus on aspects such as "Good fruit quality" and "Maintained cleanliness and hygiene," which had the highest importance values of 10.369 and 10.000, respectively. By integrating statistical analysis and HoQ, this study offers a robust framework for the sustainable development and competitiveness of Fruit Salad SMEs in the dynamic market environment of Batam City.